A11 Reviewing Progress To Date In HD. (17th September 2014) - Leavitt, B
Abstract : Huntington disease (HD) is a progressive autosomal dominant disorder, for which no disease modifying treatments are currently available. There is however, the potential to develop early therapeutic interventions that will prevent or delay disease onset; as predictive genetic testing can identify individuals who have inherited the gene mutation prior to the onset of HD symptoms. Robust biomarkers for premanifest and early HD are needed to facilitate upcoming clinical trials. Current efforts to develop biomarkers for premanifest and early HD will be reviewed, and potential clinical, cognitive, neuroimaging and biochemical biomarkers will be discussed in terms of their potential for use in HD clinical trials and utility in the development of future treatments for HD.